2009
DOI: 10.1186/1758-5996-1-22
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cardiovascular risk in patients with type 2 diabetes: a national multicenter study in Brazil

Abstract: According to Brazilian National Data Survey diabetes is the fifth cause for hospitalization and is one of the ten major causes of mortality in this country.Aimsto stratify the estimated cardiovascular risk (eCVR) in a population of type 2 diabetics (T2DM) according to the Framingham prediction equations as well as to determine the association between eCVR with metabolic and clinical control of the disease.MethodsFrom 2000 to 2001 a cross-sectional multicenter study was conducted in 13 public out-patients diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
18
2
4
Order By: Relevance
“…Concordantemente, un estudio multicéntrico brasileño, también de tipo observacional-transversal, reportó recientemente una prevalencia global de ECVA de 21,6% en PD 15 .…”
Section: Discussionunclassified
“…Concordantemente, un estudio multicéntrico brasileño, también de tipo observacional-transversal, reportó recientemente una prevalencia global de ECVA de 21,6% en PD 15 .…”
Section: Discussionunclassified
“…Type 2 diabetes mellitus is a common health problem associated with cardiovascular disease, with an increasing incidence worldwide (Gomes et al, 2009), and hypertension is an extremely common co-morbid condition in diabetes, affecting more than 50% of patients with diabetes mellitus (Marques et al, 2002). In recent years, clinical trials have demonstrated the effectiveness of aggressive treatment of hypertension in reducing macrovascular and microvascular diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Central obesity was assessed by using WC (waist circumference), WHR and WHtR standard criteria. [15][16][17] Blood pressure, systolic (SBP) as well as diastolic (DBP), was recorded using anaeroid sphygmomanometer and stethoscope as recommended by the American Heart Association. 18,19 Patients were stratified into hypertensive and prehypertensive based on the definition of the Seventh Report, Joint National committee on prevention, detection, evaluation, and treatment of high blood pressure.…”
Section: Methodsmentioning
confidence: 99%